Undoing Suicidism: A Trans, Queer, Crip Approach to Rethinking (Assisted) Suicide by Alexandre Baril - Morrill, Katharine (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
Suicide prevention initiatives and strategies commonly focus on a curative and rehabilitative approach, which often causes harm to the suicidal subject and negates their lived experience and feelings. In Undoing Suicidism: A Trans, Queer, Crip Approach to Rethinking (Assisted) Suicide, Alexandre Baril challenges dominant attitudes towards suicide, discusses suicidism as a form of oppression that silences the suicidal subject and delegitimizes their suffering, and proposes an affirmative interpersonal and legal approach through the lens of trans, queer, and disability studies.